تنظیم اسلامی کا تصور انقلاب :ایک مطالعہ: A Study of Tanzeem-i-Islāmī’s Concept of Revolution - Muhammad Mahmood Raza; Shafique Ahmad Khan; Taswar Hussain (Al-Qamar, 2020)
Historically, the French Revolution, the Russian Revolution and the Iranian Revolution are among the most important revolutions in the world. But the fact is that the only perfect revolution in the world is the "Muhammadan Revolution. This paper studies Tanzeem-i-Islāmī’s concept of revolution according to Islamic teachings and the Sīra of Prophet Muhammad. The gist of the whole debate on the concept of revolution of the Tanzeem-i-Islāmī’s is that it does not consider change in the religious field as revolution but revolution as a fundamental change in the political, economic and social system of the society. The study presents useful insights from the writings of the founder of Tanzeem-i-Islāmī, Dr. Israr Ahmad regarding the strategy for the revival of Muslim Ummah.